2011
DOI: 10.1164/rccm.201010-1596oc
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency Causes Deficits in Lung Function and Alters Lung Structure

Abstract: Vitamin D deficiency causes deficits in lung function that are primarily explained by differences in lung volume. This study is the first to provide direct mechanistic evidence linking vitamin D deficiency and lung development, which may explain the association between obstructive lung disease and vitamin D status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
240
4
9

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(264 citation statements)
references
References 46 publications
11
240
4
9
Order By: Relevance
“…Various non-vitamin D immunomodulators induced by UVR, like NO (28), may be important for the regulation of immunity (29) and obesity/MetS development (30). Skin exposure to UVR releases NO from skin (28) and could control obesity through NO-dependent effects on mitochondria biogenesis within brown adipose tissue (31).…”
Section: Discussionmentioning
confidence: 99%
“…Various non-vitamin D immunomodulators induced by UVR, like NO (28), may be important for the regulation of immunity (29) and obesity/MetS development (30). Skin exposure to UVR releases NO from skin (28) and could control obesity through NO-dependent effects on mitochondria biogenesis within brown adipose tissue (31).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that vitamin D has a role in lung growth, preserving lung function, and preventing pulmonary infection (1)(2)(3)(4)(5)(6)(7). The largest study comes from the Third National Health and Nutrition Examination Survey (NHANES III) data, which showed in healthy adults those with the highest 25-hydroxyvitamin D (25-OHD) levels had significantly higher FVC and FEV 1 than those with the lowest 25-OHD levels (3).…”
mentioning
confidence: 99%
“…The offspring of the vitamin D deficient mice -also deficient in vitamin D -had statistically significantly smaller lungs than normal: about 18% smaller in female offspring and 28% smaller in males 7 . "Our point was that vitamin D deficiency isn't causing gross structural changes in the lung, but it might be slowing down lung growth, " Zosky says.…”
Section: Deficiency As Cause?mentioning
confidence: 97%
“…The decline was so steep it is comparable to the effects of smoking 6 . And a 2011 study in mice found that vitamin D deficiency causes deficits in lung function 7 .…”
Section: Searching For Proofmentioning
confidence: 99%